Juridical Analysis of Tax Criminal Law Enforcement: an Overview of Legal Regulations and its Implementation in Indonesia - Heriantonius Silalahi (Yayasan Ilomata, 2023)
The purpose of this research is to conduct a juridical analysis of criminal law enforcement in the field of taxation in Indonesia. The focus of this study is to evaluate the effectiveness of legislation and its implementation in combating tax crimes. The research method used is a normative juridical approach by examining legislation related to tax crimes, including tax laws, government regulations, and relevant policies. Additionally, an analysis of the legal practices and enforcement of tax crimes in Indonesia is conducted. The research findings indicate that the legislation in the field of taxation has a strong foundation to address tax crimes. However, there are several challenges in its implementation, such as the complexity of tax regulations, lack of adequate human resources and technology, and corruption issues that can affect tax law enforcement. In this context, the research provides recommendations to strengthen the system of criminal law enforcement in tax matters. The recommendations include improving coordination among relevant institutions, enhancing the capacity of human resources in the field of taxation, utilizing information technology to support supervision and tax law enforcement, and increasing transparency and accountability in the process of tax law enforcement. This research is expected to provide a better understanding of the regulation of tax crimes and contribute to the policy and the legislative reforms related to tax law enforcement in Indonesia?